Introduction of database concept courseware evaluation using one-group pre-test post-test experimental design - Bahrudin, Ida Aryanie; Abdul Hamid, Mariam; Mohd Dzulkifli, Syarizul Amri; Abdullah, Mohd Ezree (American Scientific Publishers, 2017)
The 21st century education has opened new possibilities for increasing the effectiveness of teaching and learning processes through the use of information and communication technology (ICT). One of the most promising is the animation-based learning environment. Recently, animated infographics are one of the most popular approaches of presenting information in courseware. In learning information system course, database technologies are foundation in developing information systems. Thus, database concept is important for understanding a good data model and an effective database implementation. However, the abstract nature of database concept can make it challenging to teach and challenging to learn. One way to address this challenge is through the use of software animations to support the teaching of database design as well as other database related concepts. The research began with developing an infographic animated module of teaching and learning for introducing database concept to learners. Experimental research with group of student that use traditional approach as pre-test sample which later introduced by the use of courseware as post-test sample was implemented. There were 150 students of Diploma in Information Technology attending the Database Course (DAT 20404) take part in this research. In this scope of study, it can be concluded that learning through the use of courseware as teaching aid was more encouraging learning than that traditional approach.